2001
DOI: 10.1073/pnas.221458698
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the Drosophila immune response by using oligonucleotide microarrays

Abstract: To identify new Drosophila genes involved in the immune response, we monitored the gene expression profile of adult flies in response to microbial infection by using high-density oligonucleotide microarrays encompassing nearly the full Drosophila genome. Of 13,197 genes tested, we have characterized 230 induced and 170 repressed by microbial infection, most of which had not previously been associated with the immune response. Many of these genes can be assigned to specific aspects of the immune response, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
663
7
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 656 publications
(720 citation statements)
references
References 33 publications
47
663
7
3
Order By: Relevance
“…Genetic experiments indicate that natural infection of Drosophila by this fungus leads to the expression, via the selective activation of the Toll pathway, of genes encoding antifungal activity [42]. Microarray analysis also confirms that infection by this fungus leads to a more specific immune response, compared with infection by bacterial injection [19 …”
Section: Monitoring the Drosophila Immune Response After Different Momentioning
confidence: 75%
“…Genetic experiments indicate that natural infection of Drosophila by this fungus leads to the expression, via the selective activation of the Toll pathway, of genes encoding antifungal activity [42]. Microarray analysis also confirms that infection by this fungus leads to a more specific immune response, compared with infection by bacterial injection [19 …”
Section: Monitoring the Drosophila Immune Response After Different Momentioning
confidence: 75%
“…The proenzyme cathepsin L of Drosophila melanogaster was upregulated after bacterial challenge [44]. The expression of cathepsin L increased in the hepatopancreas of Mytilus galloprovincialis by treatment with the mixtures of heavy metals [45], and rose in Strongylocentrotus purpuratus after LPS stimulated [46].…”
Section: Discussionmentioning
confidence: 98%
“…This perplexing result is reminiscent of the embryonic lethality observed in dnase II-knockout mice which is caused by an unexpected overexpression of INF-β by macrophages [10][11][12]. Apart from antimicrobial peptide induction, it has been demonstrated that dDNase II itself is significantly induced by bacterial and fungal infection [41,42]. Since DNase II enzymes can be secreted into the extracellular environment [1], overexpression and secretion of dDNase II may enhance the degradation of released bacterial DNA not yet been cleared by phagocytes.…”
Section: Discussionmentioning
confidence: 99%